Growing lettuce under multispectral light-emitting diodes lamps with adjustable light intensity - Tosti, Giacomo; Benincasa, Paolo; Cortona, Rossano; Falcinelli, Beatrice; Farneselli, Michela; Guiducci, Marcello; Onofri, Andrea; Pannacci, Euro; Tei, Francesco; Giulietti, Mario (Italian Journal of Agronomy, 2017)
Light-emitting diodes (LEDs) technology offers vast possibilities in plant lighting due to its ability to mix different light frequencies, high energy use efficiency and low heat production combined to long lifespan. In particular, the combined effect of the Blue:Red (B:R) ratio and other frequencies in the central part of the PAR spectrum (CGA, i.e. cyan, green and amber) may be very important, though literature information is scarce. In this paper, the effects of six light spectra from LED technology were tested, i.e.: i) B:R=0.82 (i.e. similar to sunlight) with CGA (treatment T0); ii) B:R=0.82 without CGA (T1); iii) red prevalence (B:R=0.25) without CGA (T2); iv) blue prevalence (B:R=4) without CGA (T3); v) red prevalence with CGA (T4); and vi) blue prevalence with CGA (T5). The experiment was carried out in a walk-in climatic chamber with controlled temperature and relative humidity and an incident PAR photon flux density (PFD) of 300 μmol m–2 s–1 (14/10 light/dark photoperiod), generated by multispectral LED lamps with adjustable light intensity. Smooth leaved lettuce (Lactuca sativa L. cv Gentilina) was used as the test plant and biomass yield (DW, g m–2), LAI, soil coverage proportion (SC%), energy-biomass conversion efficiency (E-BCE, kWh g–1) and radiation use efficiency (RUE, g mol–1 photons) were determined. Treatments with red predominance (T2 and T4) showed the highest SC% rates, while those with blue predominance (T3 and T5) showed the lowest. Light spectrum also affected leaf size (i.e. mean leaf area). The highest DW and RUE were observed in T2 and T4, followed by T0, while biomass in T3 and T5 was significantly lower (similar to T1). LAI values were generally high, but treatments with blue predominance showed the lowest LAI values (both with or without CGA). The introduction of intermediate wavelengths (green, cyan and amber) did not bring about significant improvement in DW or RUE, but resulted in reduced energy-biomass conversion efficiency, mainly due to lower architectural efficiency of the CGA LEDs. Future research should clarify how to optimise the light spectra according to the crop growth phases. The adoption of spectra promoting fast growth is fundamental in the early growth, while the use of spectra maximising yield quality may be more important later on.